2015
DOI: 10.1093/jee/tov333
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection and Evaluation for Gene Expression Studies Using qRT-PCR in the White-Backed Planthopper,Sogatella furcifera(Hemiptera: Delphacidae)

Abstract: The white-backed planthopper, Sogatella furcifera (Hemiptera, Delphacidae), is one of the most devastating rice pests. For a better control strategy, various genetic studies have been conducted using reverse-transcription quantitative real-time polymerase chain reaction (qRT-PCR). The appropriate application of qRT-PCR requires reliable endogenous controls; however, studies on this aspect of the white-backed planthopper are lacking. In the present study, nine commonly used reference genes, elongation factor 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…RPL13a was calculated as one of the most stable RGs to phosphine induction in T. castaneum 51 , but it did not exhibit such a high degree of stability across different phosphine strains of C. ferrugineus in the present study, indicating that the stability of the same RG may be species-specific. α-TUB has also been widely used as a RG in gene expression studies in G. daurica 28 and Sogatella furcifera 36 . However, other researcher have revealed that α-TUB does not satisfy certain basic requirements for use as an internal control 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPL13a was calculated as one of the most stable RGs to phosphine induction in T. castaneum 51 , but it did not exhibit such a high degree of stability across different phosphine strains of C. ferrugineus in the present study, indicating that the stability of the same RG may be species-specific. α-TUB has also been widely used as a RG in gene expression studies in G. daurica 28 and Sogatella furcifera 36 . However, other researcher have revealed that α-TUB does not satisfy certain basic requirements for use as an internal control 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to validate the expression stability of RGs under specific experimental conditions before using them for normalization. To date, many studies have been conducted in various insect groups to select suitable RGs under different experimental conditions, such as Lepidoptera 29 , Hymenoptera 33 , Diptera 34 , Corrodentia 35 , Coleoptera 28 , Homoptera 30 , 36 , 37 , Thysanoptera 38 and Hemiptera 31 . However, none of these previous studies has focussed on C. ferrugineus , which limits the current opportunities for functional genomics studies on this important pest.…”
Section: Introductionmentioning
confidence: 99%
“…KP735521) and elongation factor 1α (SfEF1α, accession No. KP735517) using the 2 − Ct method, like previous studies (Livak and Schmittgen, 2001;An et al, 2015;Yin et al, 2018;Yue et al, 2018). Each sample had three technological replicates.…”
Section: Developmental Expression Profiles Of Sfvg and Sfvgrmentioning
confidence: 99%
“…Consequently, the selection of appropriate reference genes is critical in offsetting variations and biases (Lü et al, 2018). Recently, there has been a dramatic increase in studies of reference gene selection in the cell-content feeding arthropods, including Hemiptera ( Supplementary Table S3; Li et al, 2013;Yang et al, 2014Yang et al, , 2015bYuan et al, 2014;Shang et al, 2015;Koramutla et al, 2016;Ma et al, 2016;An et al, 2016;Yu et al, 2016;Arya et al, 2017;Kang et al, 2017), and three spider mites species (Sun et al, 2010;Niu et al, 2012;Yue et al, 2013;Yang et al, 2015a). Most of these studies in Tetranychidae species have focused on the expression patterns of reference genes under the impact of insecticide and developmental stage.…”
Section: Discussionmentioning
confidence: 99%